2020
DOI: 10.1016/j.omto.2020.03.023
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 IC Inhibition Synergistically Improves Influenza A Virus-Mediated Oncolysis of Metastatic Pulmonary Melanoma

Abstract: Recently, we showed that infection of primary lung tumorbearing mice with oncolytic influenza A viruses (IAVs) led to strong virus-induced tumor cell lysis but also to restoration of immune competence of innate immune cells. Murine B16-F10 melanoma cells are known for their high lung tropism and progressive growth. As these cells are also highly permissive for IAVs, we analyzed their oncolytic and immunomodulatory efficiency against pulmonary B16-F10 lung metastases in vivo. IAV infection abrogated the melanom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The contribution of B-cells in our model remains to be further investigated. Although B16 melanoma cells seem to be per se permissive for IAV infection in vitro [ 25 , 26 ], IAV does not replicate in the tumour in our model. Therefore, the slowed tumour growth cannot be the result of direct tumour cell lysis by the virus, but is rather immune-mediated.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of B-cells in our model remains to be further investigated. Although B16 melanoma cells seem to be per se permissive for IAV infection in vitro [ 25 , 26 ], IAV does not replicate in the tumour in our model. Therefore, the slowed tumour growth cannot be the result of direct tumour cell lysis by the virus, but is rather immune-mediated.…”
Section: Discussionmentioning
confidence: 99%
“…125 PD-L1 and PD-1 are immune checkpoint proteins involved in modulating the body's immune response. [126][127][128] Although checkpoint proteins have a role in preventing autoimmune disease, they can also suppress the immune system's ability to attack tumor cells. Research is deepening on the drug's use to inhibit the action of PD-1/PD-L1 and thereby increase the body's ability to fight tumor cells.…”
Section: Immunotherapymentioning
confidence: 99%
“…Several approaches using a variety of OVs and ICIs are in pre-clinical and clinical development. For example using a mouse model of metastatic pulmonary melanoma, it was demonstrated that virotherapy using influenza A viruses (IAVs) combined with ICI resulted in a sustained antitumor efficacy caused by the significant increase in the oncolytic effect ( Sitnik et al, 2020 ). In other lines of evidence, Vijayakumar et al, applied Newcastle disease virus (NDV) in combination with radiotherapy plus checkpoint inhibitors (PD1 or CTLA4 targeted mAbs) induces an abscopal effect in immunocompetent B16-F10 murine melanoma model.…”
Section: Combining Virotherapy With Different Immunotherapeutic Inter...mentioning
confidence: 99%